STUDI TENTANG BENTUK DAN STRUKTUR PELAMINAN DI IDAMAN PENGANTEN KOTA PARIAMAN - Sepdrian Sepdrian; Efrizal Efrizal (Universitas Negeri Padang, 2020)
This study aims to describe the from and structure of aisle in the Idaman Penganten in the city of Pariaman for the next generation. The author realizes that the current culture of Minangkabau has been shifted by the development of the times, one of which is the form and structure of the aisle used which is no longer compatible with the form of the aisle before. This research method is carried out by compiling research designs, selecting research sites, making observations directly to the research site, conducting interviews with informants to obtain data to be examined and analyzing research data that have been obtained. This study explains how the shape and structure of the Minangkabau aisle in the Pariaman city area, which is expected to be a reference for the wider community, especially for the next generation of Minangkabau culture. Then it is hoped for the nextgeneration to always preserve the culture of the Original Minangkabau.Kata kunci: Bentuk, Struktur, Pelaminan, kota Pariaman.